Faith and End of Life in Nursing Homes - Robert L. Rubinstein; Helen K. Black; Patrick J. Doyle; Miriam Moss; Sidney Z. Moss (Journal of Aging Research)
This paper explores the role of religious belief in the experiences of dying and death in a Catholic nursing home. The home appeals to residents and their families due to the active religious presence. Thus, religion is a salient element of the “local culture” which exists in this long-term care setting. The preeminence of faith within the organization and the personal religious convictions of staff, residents, and families may drive how death and dying are discussed and experienced in this setting, as well as the meanings that are attached to them. This paper examines the relationship between faith and the experience and meaning of death in this nursing home. We present themes that emerged from open-ended interviews with residents, family members, and staff, gathered between 1996 and 2004. The data indicate that people select the home due to their Catholic faith and the home's religious tone. Themes also show that belief in God and an afterlife helps shape the experience of dying and death for our informants. Our paper does not compare ease of dying with other nursing homes or within other belief systems.